Approach to gastroenterological diseases in primary care - Russo, Michele; Miraglia, Chiara; Nouvenne, Antonio; Leandro, Gioacchino; Meschi, Tiziana; de' Angelis, Gian Luigi; Di Mario, Francesco (Acta Biomedica Atenei Parmensis, 2018)
Gastroenterological diseases are a source of morbidity, mortality and costs, and have a high frequency in general practice; for this reason, we have evaluated the current literature regarding the knowledge and management of these disorders by general practitioners, finding little knowledge and adherence to guidelines, highlighting the need for continuous updating in this regard, and greater collaboration between specialists and general practitioners.